PENGARUH STRATEGI KWL (KNOW, WANT TO KNOW, LEARNED) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS FIKSI SISWA KELAS V SD NEGERI 163 LALEBATA KECAMATAN LAMURU KABUPATEN BONE - Mujahidah; Achmad Shabir; Andi Rezky Amelia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This quantitative study aims to determine the effect of the KWL strategy on the reading comprehension ability of fictional texts of fifth-grade students at SD Negeri 163 Lalebata, Lamuru District, Bone Regency. This research is a quasi-experimental study using a nonequivalent control group design. The total sample consisted of 34 students, divided into 21 students in the experimental class and 13 students in the control class. The data collection technique used was tests in the form of a pretest and posttest. The results showed that the average posttest score of the experimental class was 73.71, while the control class was 72.31. Based on the Independent Sample T-Test, the significance value obtained was 0.685 > 0.05 and tcount < ttable, thus H0 is accepted and Hₐ is rejected. The conclusion of this study is that there is no significant effect of using the KWL strategy on the reading comprehension ability of fictional texts of fifth grade students at SD Negeri 163 Lalebata.